2020
DOI: 10.1039/d0se00013b
|View full text |Cite
|
Sign up to set email alerts
|

All-solid-state Li-metal batteries: role of blending PTFE with PEO and LiTFSI salt as a composite electrolyte with enhanced thermal stability

Abstract: Enhancing the ionic conductivity and thermal stability of solid electrolytes is crucial for the development of all-solid-state batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…The curves presented in Figure d display different behaviors in the regions from 25 to 45 °C and from 45 to 65 °C. The inflection point near 45 °C is presumably due to the transformation of the PVDF/PEC blended polymer from crystalline properties to a more amorphous structure. , The amorphous phase of the polymer would promote the diffusion of Li + ions across the interchain and intrachain segments, providing many new diffusion pathways and more mobile charge carriers (because of the increased free volume) . Furthermore, it is reasonable that more Li + ion hopping sites were formed, thereby increasing the Li + ionic conductivity upon increasing the temperature.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The curves presented in Figure d display different behaviors in the regions from 25 to 45 °C and from 45 to 65 °C. The inflection point near 45 °C is presumably due to the transformation of the PVDF/PEC blended polymer from crystalline properties to a more amorphous structure. , The amorphous phase of the polymer would promote the diffusion of Li + ions across the interchain and intrachain segments, providing many new diffusion pathways and more mobile charge carriers (because of the increased free volume) . Furthermore, it is reasonable that more Li + ion hopping sites were formed, thereby increasing the Li + ionic conductivity upon increasing the temperature.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The morphology of the polymer film after combustion demonstrated thermal stability against the extreme case. Jokhakar et al 56 conducted a polymer flammability test on PEO‐PTEE systems (Figure 4(A)). After burning, PEO completely melted, which may lead to a short circuit in practical ASSLIBs, but the CPE mixed with PTEE reflects dramatically less flammability.…”
Section: Material‐level Thermal Stability Of Sesmentioning
confidence: 99%
“…The battery with polymer electrolyte showed better thermal stability with smaller heat generation. Jokhakar et al 56 choose the same anode to compare liquid electrolyte with polymer ASSLIB, and found that SEs produced less heat than the liquid electrolyte. The total heat productions of batteries with liquid, PEO, and PTFE‐modified electrolytes were 5473, 3554, and 1970 kJ g −1 , respectively (Figure 12(B)).…”
Section: Battery‐level Thermal Stabilitymentioning
confidence: 99%
“…Linear poly­(ethylene oxide) (PEO) has gained significant attention as an SPE , due to its excellent characteristics including fast segmental dynamics as well as the ability to form complexes with a wide range of different lithium salts. It is generally believed that ion conduction occurs in the amorphous phase where ion transport is coupled with segmental dynamics. ,,, At room temperature, however, PEO is a semicrystalline polymer with ionic conductivity ranging between 10 –6 and 10 –8 S/cm, in which crystalline regions impede ion transport (see Figure a for scheme). The ionic conductivity increases up to 10 –3 S/cm above its melting temperature ( T m = 60 °C), yet with severe reduction in mechanical strength, which limits its application in a solid-state battery.…”
Section: Introductionmentioning
confidence: 99%
“…The ionic conductivity increases up to 10 –3 S/cm above its melting temperature ( T m = 60 °C), yet with severe reduction in mechanical strength, which limits its application in a solid-state battery. To overcome these drawbacks in relation to crystallization and mechanical stability, one method is to blend PEO with another polymer that can provide mechanical rigidity and eliminate crystallinity. , In this sense, a high glass transition temperature ( T g ) polymer poly­(methyl methacrylate) (PMMA) is commonly used (Figure b). Incorporation of PMMA into PEO significantly increased the mechanical properties, such as storage modulus, of PEO/PMMA blends, making the liquid-like behavior of PEO to a more solid-like behavior. , …”
Section: Introductionmentioning
confidence: 99%